Adsorption of Heavy Metal Chromium (Cr) Using Pineapple Skin Filtrate with the Chelation Method - Al Dina Khoerunisa NM; Anisa Afifatul Azizah; Andika Adhi Setianingsih (Formosa Journal of Applied Sciences, 2022)
Many methods of treating heavy metal waste have been carried out, one of which is adsorption. With this method, heavy metal ions can form a coordination complex with carboxyl groups (-COO) from adsorbents made from natural materials. The purpose of this study was to determine the effect of varying concentrations of pineapple peel filtrate as a natural adsorbent and mixing time with chromium metal (Cr) in a simulated waste solution. Simulated chromium (Cr) waste solution with a concentration of 10 ppm was mixed with pineapple peel filtrate at various concentrations of 25%, 50%, 75%, and 100% (w/v) for 30 minutes and 60 minutes and then analyzed using Atomic Absorption Spectrophotometry (AAS). ). The research results obtained showed that pineapple peel filtrate was effective in reducing chromium (Cr) metal content in the simulated waste solution. The highest percentage of reduction in chromium (Cr) metal content exceeds 100%, namely at a concentration of 100% pineapple skin filtrate during a mixing time of 60 minutes.